ANALYSIS OF INTRINSIC VALUE AND INSTRUMENTAL VALUE OF DEMOCRACY IN PRESIDENTIAL THRESHOLD - Jefrino-Fahik, Antonius (Politik Indonesia: Indonesian Political Science Review, 2024)
This article aims to discuss the presidential threshold in the process of nominating president and vice president in Indonesia with the concept of the values of democracy introduced by Adam Swift (2014). In contrast to the dominant legal-normative approach which views the presidential threshold from its pros and cons, this paper uses a political philosophy perspective which sees that the position of pros and cons are related to each other. Starting from the assumption of the values of democratic, the author sees that the debate (pros and cons) reflects the intrinsic and instrumental value of democracy. To understand the relationship between the pros and cons with the values of democratic, this research uses qualitative methods with a literature study approach. The analysis shows that, tension between pros and cons do not negate each other, but inevitably presuppose each other. This study concludes that the presidential threshold should be lowered to 5% of seats in parliament and 10% of the valid national vote to accommodate all interests.